(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Survey the process of looking up cosmetic formula ingredients at the Ho Chi Minh City Department of Health; develop and evaluate software for looking up ingredient formulas in cosmeceuticals. Methods: The study surveys the process and data sources for looking up cosmetic ingredient formulas within the management of cosmetics at the Ho Chi Minh City Department of Health. Development of the software Phasolpro DMP v1.0 involves proposing User requirements specification (URS), interface design, programming, and software identification. The software qualifiation is based on the URS and validation is based on a realistic case. Results: The process of looking up cosmetic formula ingredients utilizes data from two sources: The EU CosIng of the European Commission database and the annexes of the ASEAN Cosmetic Directive. Specialists evaluate registration documents to ensure compliance with lists of banned or restricted substances, and permissible colorants, preservatives, and UV filters. URS was proposed and the interfaces were designed for the software Phasolpro DMP v1.0. The software features include batch searches, detailed information providing, duplication warnings, spell check, and substance name suggestions. Software qualification and validation results indicate that the software met the requirements of the proposed URS and worked as designed. Conclusion: Develop look up software Phalsopro DMP v1.0 for formula ingredients in pharmaceutical and cosmetic products that met requirements and passed software validation.